Nitrogen Addition Affects Ecosystem Carbon Exchange by Regulating Plant Community Assembly and Altering Soil Properties in an Alpine Meadow on the Qinghai–Tibetan Plateau - Han, Ling; Ganjurjav, Hasbagan; Hu, Guozheng; Wu, Jianshuang; Yan, Yulong; Danjiu, Luobu; He, Shicheng; Xie, Wendong; Yan, Jun; Gao, Qingzhu (Frontiers in Plant Science, 2022)
Nitrogen (N) deposition can affect the global ecosystem carbon balance. However, how plant community assembly regulates ecosystem carbon exchange in response to N deposition remains largely unclear, especially in alpine meadows. Here, we conducted a manipulative experiment to examine the impacts of N (ammonium nitrate, NH4NO3) addition on ecosystem CO2 exchange by changing the plant community assembly and soil properties at an alpine meadow site on the Qinghai-Tibetan Plateau (QTP) from 2014 to 2018. The N-addition treatments were N0, N7, N20 and N40 (0, 7, 20, and 40 kg N ha-1yr-1) during the plant growing season. Net ecosystem CO2 exchange (NEE), gross ecosystem productivity (GEP), and ecosystem respiration (ER) were measured by a static chamber method. Our results showed that the growing-season NEE, ER and GEP increased gradually over time with increasing N-addition rates. On average, the NEE increased significantly by 55.6% and 65.2% in N20 and N40, respectively (P < 0.05). N addition also increased forage grass biomass (GB, including sedge and Gramineae) by 74.3% and 122.9% and forb biomass (FB) by 73.4% and 51.4% in N20 and N40, respectively (P < 0.05). There were positive correlations between CO2 fluxes (NEE and GEP) and GB (P < 0.01), and the ER was positively correlated with functional group biomass (GB and FB) and soil available N content (NO3–N and NH4+-N) (P < 0.01). The N-induced shift in the plant community assembly was primarily responsible for the increase in NEE. The increase in GB mainly contributed to the N stimulation of NEE, and FB and the soil available N content had positive effects on ER in response to N addition. Our results highlight that the plant community assembly is critical in regulating the ecosystem carbon exchange response to N deposition in alpine ecosystems